Restoring Akt1 Activity in Outgrowth Endothelial Cells From South Asian Men Rescues Vascular Reparative Potential. (October 2014) - Cubbon, Richard M.; Yuldasheva, Nadira Y.; Viswambharan, Hema; Mercer, Ben N.; Baliga, Vivek; Stephen, Sam L.; Askham, Jonathan; Sukumar, Piruthivi; Skromna, Anna; Mughal, Romana S.; Walker, Andrew M.N.; Bruns, Alexander; et al.
Abstract Recent data suggest reduced indices of vascular repair in South Asian men, a group at increased risk of cardiovascular events. Outgrowth endothelial cells (OEC) represent an attractive tool to study vascular repair in humans and may offer potential in cell‐based repair therapies. We aimed to define and manipulate potential mechanisms of impaired vascular repair in South Asian (SA) men. In vitro and in vivo assays of vascular repair and angiogenesis were performed using OEC derived from SA men and matched European controls, prior defining potentially causal molecular mechanisms. SA OEC exhibited impaired colony formation, migration, and in vitro angiogenesis, associated with decreased expression of the proangiogenic molecules Akt1 and endothelial nitric oxide synthase (eNOS). Transfusion of European OEC into immunodeficient mice after wire‐induced femoral artery injury augmented re‐endothelialization, in contrast with SA OEC and vehicle; SA OEC also failed to promote angiogenesis after induction of hind limb ischemia. Expression of constitutively active Akt1 (E17KAkt), but not green fluorescent protein control, in SA OEC increased in vitro angiogenesis, which was abrogated by a NOS antagonist. Moreover, E17KAkt expressing SA OEC promoted re‐endothelialization of wire‐injured femoral arteries, and perfusion recovery of ischemic limbs, to a magnitude comparable with nonmanipulated European OEC. Silencing Akt1 in European OEC recapitulated the functional deficits noted in SA OEC. Reduced signaling via the Akt/eNOS axis is causally linked with impaired OEC‐mediated vascular repair in South Asian men. These data prove the principle of rescuing marked reparative dysfunction in OEC derived from these men. Stem Cells2014;32:2714–2723